Pengaruh Kualitas Produk, Harga, dan Citra Merek terhadap Niat Beli Handphone Samsung - Nurmala, Elva; Saputro, Edy Purwo (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine the effect of product quality, price, and brand image on purchase intention of Samsung cellphones. The method used in this research is quantitative method. The population and samples in this study were consumers who had never made a purchase on a Samsung mobile phone that met the requirements and the number of respondent sampled in this study were 100 respondents. The data source in this study in this study is primary data with the measurement scale used is 5 likert scale. Data analysis using SmartPLS 3 software. The results of the analysis in this study indicate that product quality and price have a positive and significant effect on purchase intention, while brand image has a negative and insignificant effect on purchase intention.